Field efficacy of anticoagulant rodenticide towards managing rodent pests in Jitra rice field, Kedah, Malaysia - Burhanuddin, Maisarah; Mohd Noor, Hafidzi; Salim, Hasber; Asrif, Nur Athirah; Jamian, Syari; Azhar, Badrul (Penerbit Universiti Sains Malaysia, 2024)
Frequent encounters with the greater bandicoot rats (Bandicota indica) following high rodent damage towards rice crops and lack of information on the species had encouraged this study to be conducted to test the relevance of using first-and second-generation rodenticide in a field efficacy test. This study also attempts to detect any sign of resistance of current rodent pest populations towards chlorophacinone (0.005%) and flucoumafen (0.05%) for the control of field rats predominant rice field agrosystem of the Kedah in northern peninsular Malaysia. Six different treatments over dry and wet rice planting season together with trapping exercise. The observation was evaluated based on the number of active burrows, counting tiller damage due to rodent attack and trapping index. The results indicated that flucoumafen gives better rodent control and has a better impact (p < 0.05) although chlorophacinone is still relevant to be applied (p < 0.05). Treatments during the off-planting season (September–February) are more effective compared to the main planting season (March–August). Rodent control during the early off-planting season is encouraged for better rodent management in the rice field and the use of bait stations to increase the weatherability of the baits.